2014
DOI: 10.7763/ijiet.2014.v4.405
|View full text |Cite
|
Sign up to set email alerts
|

Child and Family Predictors of Child-Teacher Relationship Trajectories during the Transition from Preschool to School

Abstract: Abstract-This longitudinal study aimed to identify child, socio-demographic, family, and relationship factors associated with children's teacher relationship quality trajectories over the transition from preschool into school. A community sample of 636 Australian children were assessed in preschool, the first year, and second year of formal schooling. Teachers at all three assessments reported on child-teacher relationship quality. At preschool, teachers and parents reported on children's mental health difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(84 reference statements)
2
6
0
1
Order By: Relevance
“…Knowledge of risk factors associated with poor student-teacher relationship trajectories may also usefully suggest potential targets for interventions (Zhang and Sun 2011 ). Research with this sample (Miller-Lewis et al 2014 ) and others (O’Connor 2010 ; O’Connor and McCartney 2007 ; O’Connor et al 2012 ; Jerome et al 2009 ) has found that these risk factors include being a boy, poorer social skills, significant mental health problems in preschool, exposure to poorer parenting, low maternal education, poor classroom management, and having a poorer quality relationship with kindergarten teachers. Knowledge on such risk factors for poor quality student-teacher relationship trajectories would be useful to impart in teacher training and professional development, as this knowledge may make teachers more mindful of counteracting this possibility by consciously adjusting the frequency and type of their interactions with children who could be considered at-risk for poorer quality relationships.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Knowledge of risk factors associated with poor student-teacher relationship trajectories may also usefully suggest potential targets for interventions (Zhang and Sun 2011 ). Research with this sample (Miller-Lewis et al 2014 ) and others (O’Connor 2010 ; O’Connor and McCartney 2007 ; O’Connor et al 2012 ; Jerome et al 2009 ) has found that these risk factors include being a boy, poorer social skills, significant mental health problems in preschool, exposure to poorer parenting, low maternal education, poor classroom management, and having a poorer quality relationship with kindergarten teachers. Knowledge on such risk factors for poor quality student-teacher relationship trajectories would be useful to impart in teacher training and professional development, as this knowledge may make teachers more mindful of counteracting this possibility by consciously adjusting the frequency and type of their interactions with children who could be considered at-risk for poorer quality relationships.…”
Section: Discussionmentioning
confidence: 82%
“…In multivariate analyses, we adjusted for several potential confounders of the association between children’s student-teacher relationship trajectories and children’s mental health scores in the second school year. These confounders were identified on the basis of evidence from previous studies describing factors that may influence children’s relationship with their teachers and their mental health problems (e.g., Amato 2001 ; Beardslee et al 1998 ; Bradley and Corwyn 2002 ; Fergusson and Horwood 2001 ; Howes 2000 ; O’Connor and McCartney 2006 , 2007 ; O’Connor et al 2012 ; Jerome et al 2009 ; Spilt et al 2012a ; Ladd et al 1999 ; Pianta and Stuhlman 2004 ; Miller-Lewis et al 2013 ; Miller-Lewis et al 2014 ), and a priori on the basis of Directed Acyclic Graphs, which are visual diagrams summarising assumptions regarding potential causal links between variables (Greenland et al 1999 ). In the final analysis models we also adjusted for the child’s corresponding SDQ scores (informant-specific) at age 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that include first-graders in their examination of the development of trajectories of the teacher–student relationship are more common than for the parent–child relationship. For instance, Miller-Lewis et al (2014) followed teacher reports of their relationships with children throughout preschool to Grade 2 and found two trajectories: stable-high quality and moderate declining quality of overall relationship scores (in terms of closeness and reversed conflict). Other studies typically find more than two trajectories ( O’Connor et al, 2011 ; Spilt et al, 2012 ; Valiente et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As there is little previous research in this area, and since what there is reports mixed findings for the teacher–student relationship (including different numbers of profiles and their transitions, none of which include parents), we based our expectations on variable-oriented research and person-oriented research of children’s relationships with teachers. We expected that the largest profile would be adaptive and consist of students who enjoy a good (average) quality of relationships with both their parents and teachers ( Spilt et al, 2012 ; Miller-Lewis et al, 2014 ; Heatly and Votruba-Drzal, 2017 ; Valiente et al, 2019 ). Additionally, we expected to find one or more non-adaptive profiles ( Spilt et al, 2012 ; Miller-Lewis et al, 2014 ; Heatly and Votruba-Drzal, 2017 ; Valiente et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%